Diversity of pathogenicity among rice blast fungus (Pyricularia oryzae) isolates in Bangladesh (Bangladesh Rice Journal, 2026)
A study was undertaken to determine the pathogenic and the genetic diversity of Pyricularia oryaesolates causing blast disease of rice in Bangladesh. To find out pathogenic diversity of P.  oryzae), 100 isolates were collected from five agro ecological zones (AEZ) abbreviated as AEZ23, AEZ19, AEZ13, AEZ28 and AEZ2 of Bangladesh. They were tested for their pathogenicity against 26 rice (Oryza sativa L.) differential varieties (DVs) having 23 resistance genes designated as Pish, Pib, Pit, Pia, Pii, Pi3, Pi5(t), Pik-s, Pik-m, Pi1, Pik-h, Pik, Pik-p, Pi7(t), Pi9, Piz, Piz-5, Piz-t, Pita-2, Pita, Pi12(t), Pi19, and Pi20(t). The virulence analysis showed that four genes, Pish, Pi9, Piz and Pita-2 revealed a wide spectrum of moderate resistance to those isolates. The isolates were categorized into 94 races on the basis of the reaction patterns against rice differential varieties harboring twenty-three resistance genes and one susceptible variety, Lijiangxintuanheigu (LTH) by latest designation system. The findings demonstrate the existence of a wide variation in blast pathogens in Bangladesh. The average virulence of isolates from individual AEZ reveals that the maximum virulent isolates occur in AEZ2 (67%) followed by AEZ19 (63%) and AEZ28 (55%). Moreover, 100 Pyricularia oryzae  isolates were grouped into five clusters viz. I, II, III, IV and V based on results of the pathogenicity on 26 differential varieties including LTH on the basis of principal component analysis. Cluster I comprised of 18 isolates. Cluster II contained maximum of 31 isolates and cluster III contained 16 isolates. 23 isolates were placed in cluster IV and 12 isolates belonged to cluster V. The average virulence frequency of five Cluster I, II, III, IV and V showed 50%, 63%, 57%, 59% and 56% respectively. The findings of the present study reveal that the monogenic lines selected as differential varieties and the representative 25 blast isolates primarily selected 25 blast  isolates may be used as the first differential system, which can be used to characterize the resistance of rice varieties.Bangladesh Rice J.28(1): 57-68